The politics of resource allocation and control in Nigeria (2014)
Over the past four decades, revenue allocation and resource control has been a controversial issue in Nigeria body politics. The distribution of power between the central government and the constituent units, and the appropriate modalities for the distribution of natural resources remain highly contentious issues in Nigeria. This paper examines oil as a source of power and wealth within the context of Nigeria’s federalism. The prevailing concept of federalism in Nigeria today falls short of expectation in both definition and practice. The paper argues that the centralization of power structure by the military distorted Nigeria’s federalism. The increased fiscal centralization has made the centre very attractive. The concentration phenomenon has promoted unhealthy competition with each region attempting to have effective control of the government at the centre: Thus, the agitation for resource control in Nigeria is also part of the politics of resource allocation. The paper concludes that federalism is the most suited system of governance in Nigeria and there is the need to place emphasis on a constitutional reform in the struggle for resource control and revenue allocation in Nigeria